NaHCO3 as a carrier of CO2 and its enhancement effect on mineralization during hydrothermal alteration of basalt - Kikuchi, Sena; Wang, Jiajie; Dandar, Otgonbayar; Uno, Masaoki; Watanabe, Noriaki; Hirano, Nobuo; Tsuchiya, Noriyoshi (Frontiers in Environmental Science, 2023)
Reaction of carbon dioxide (CO2) with minerals to generate stable carbonates, also known as CO2 mineralization, has been regarded as one of the most promising methods for safe and permanent carbon storage. As a promising feedstock, basaltic rock has gained special interest, and elevating basalt carbonation efficiency with the reduction of negative environmental impact is the main challenge for CO2 mineralization system development. Considering multiple potential positive effects of the CO2 carrier, NaHCO3, we conducted this study to experimentally evaluate the CO2 storage efficiency during water-basalt-NaHCO3 interactions under hydrothermal conditions at 200−300 ℃. The use of Na and CO2-rich water was confirmed to drastically promote the alteration of basalt, especially at higher temperatures. The CO2 storage efficiency at 300 ℃ reached 75 g/kg of basalt in 5 days, which was 12.1 times higher than that at 200 °C. In such hydrothermal systems, basalt was carbonated to generate calcite (CaCO3), where the Ca was mainly from plagioclase; Mg and Fe were incorporated into smectite, and Na in the saline system participated in the formation of Na silicates (i.e., analcime in the case of basalt). Due to the presence of additional Na in solution, all the released elements were consumed quickly with generation of secondary minerals in turn promoted basalt dissolution to release more Ca for CO2 storage. This study illuminated the role of NaHCO3 in basalt carbonation and provided technical backup to the design of advanced CO2 mineralization systems.